UMPSA forms strategic collaboration with 12 industries involving Work-Based Learning (WBL) - Mimi Rabita, Abdul Wahit (UMPSA, 2023)
PUTRAJAYA, August 25, 2023 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) has established a strategic partnership with 12 industrial organizations to strengthen ties between academia and various fields, including staff engagement, research, and development, benefiting both parties.